The Effect of Stock Market Capitalization on Economic Growth in Kenya - Evan, Okisa (International Journal of Finance Research, 2022)
This study examined the effect of stock market capitalization on economic growth in Kenya. The study adopted explanatory research design that is quantitative. The study was guided by neoclassical endogenous growth theory. The major sources of data were national accounts data from the Kenya National Bureau of Statistics (KNBS) Economic Surveys, Statistical Abstracts and International Financial Statistics (IFS) site for the period 1990-2021. The study used a vector error correction model. The variables were first tested for unit root thereafter Johansen cointegration Technique was used to test the long run relationship of the variables. The study found that there were unit roots at levels but became stationary after first difference. Results showed that stock market capitalization had a negative and significant long run relationship on economic growth in Kenya (β= -0.148, p<0.05). The capital market authority may relax the listing requirements to enable more firms get listed in Nairobi Securities Exchange to strengthen growth stock markets capitalization and therefore spur economic growth